EQUIPAMENTOS PÚBLICOS DE LAZER, MEMÓRIA, AFETIVIDADE E O PLANO DIRETOR EM UMA CIDADE AMAZÔNICA: UMA VISÃO JACOBSIANA - Oliveira, Antonio Passos de; Rodrigues, João; Silva, Eduarda; Oliveira Junior, Juscelino (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The Amazonian cities present, as a result of their unbalanced structuring process, several urban problems. In Jane Jacobs's view interventions through urban reforms should consider the categories, sidewalk, street, block, neighborhood and squares. More than half a century after the consecration of this author's works, and a decade after the implementation of the Master Plan of the city of Marabá, State of Pará, Eastern Amazonia, Brazil, one perceives a misalignment between the adopted measures of intervention in the constructed environment, and consideration with users. This work presents an analysis of three leisure facilities in this city, demonstrating the incongruity between the planned actions and the reality of the places. An ethnographic study seeks not only to present the mismatch of interventions with the real needs of the residents, but, as it is crucial to seek ways of insertion of the residents in the decisionmaking process, not only at the time of the preparation of the Master Plan, during the implementation of its actions. Thus, this work evidences the need for participatory mechanisms, in the decision-making process, to be able to incorporate the residents' goals, achieving more adherence and that actions are indeed perceived and welcomed.